2020
DOI: 10.1182/bloodadvances.2020001569
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of 35 RHD variants in 16 253 serologically D− pregnant women in the Finnish population

Abstract: Fetal RHD screening for targeted routine antenatal anti-D prophylaxis has been implemented in many countries, including Finland, since the 2010s. Comprehensive knowledge of the RHD polymorphism in the population is essential for the performance and safety of the anti-D prophylaxis program. During the first 3 years of the national screening program in Finland, over 16 000 samples from RhD− women were screened for fetal RHD; among them, 79 samples (0.5%) containing a maternal variant allele were detected. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…11,23 Currently used methods in RHD genotyping, PSR-SSP, and Sanger sequencing are insufficient to identify many variant alleles, especially intronic variations. 30 We suggest additional gene investigation not covered in this study including yet unexplored regions of regulation and intron regions to justify our serological finding.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…11,23 Currently used methods in RHD genotyping, PSR-SSP, and Sanger sequencing are insufficient to identify many variant alleles, especially intronic variations. 30 We suggest additional gene investigation not covered in this study including yet unexplored regions of regulation and intron regions to justify our serological finding.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, it is hard to quantify the number of antigen sites able to elicit the immune response, but studies showed it can be as low as 30 D antigen sites 11,23 . Currently used methods in RHD genotyping, PSR‐SSP, and Sanger sequencing are insufficient to identify many variant alleles, especially intronic variations 30 . We suggest additional gene investigation not covered in this study including yet unexplored regions of regulation and intron regions to justify our serological finding.…”
Section: Discussionmentioning
confidence: 78%
“…Such a limitation can be overcome by short-read sequencing based on PCR enrichment, discriminating between homologous regions or long-read sequencing such as nanopore sequencing. A short-read sequencing method based on long-range PCR enrichment, specifically amplifying the RHD gene, has already been described [18, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Transfusing blood donation from these individuals to RhD negative recipients can risk formation of anti-D. Consequently, many countries routinely use genotyping to identify RHD variants in donors and recipients. [5][6][7] The management of pregnancies of women with variant RhD phenotypes is complicated by the fact that routine cff DNA testing cannot accurately predict the RhD phenotype of the fetus due to the presence of a maternal RHD gene. The fetus may express epitopes of RhD that the mother lacks, causing alloimmunisation and therefore anti-D prophylaxis should be offered.…”
Section: Dear Editormentioning
confidence: 99%